Free-ranging avifauna as a source of generalist parasites for captive birds in zoological settings: An overview of parasite records and potential for cross-transmission - Játiva, Patricio D Carrera; Morgan, Eric R; Barrows, Michelle; Uzcátegui, Gustavo Jiménez; Tituaña, Jorky Roosevelt Armijos (Journal of Advanced Veterinary and Animal Research, 2020)
Captive birds in zoological settings often harbor parasites, but little information is available about the potential for free-ranging avifauna to act as a source of infection. This review summarizes the gastrointestinal parasites found in zoo birds globally and in seven common free-ranging avian species [mallard (Anas platyrhynchos), Eurasian blackbird (Turdus merula), common starling (Sturnus vulgaris), Eurasian jackdaw (Corvus monedula), house sparrow (Passer domesticus), European robin (Erithacus rubecula), and rock dove (Columba livia)] to identify the overlap and discuss the potential for cross-species transmission. Over 70 references were assessed, and papers spanned over 90 years from 1925 to 2019. A total of 60 studies from 1987 to 2019 met the eligibility criteria. All examined free-ranging avifauna harbored parasite species that were also reported in zoo birds, except for the European jackdaw. Parasites reported in captive and free-ranging birds include nematodes (Capillaria caudinflata, Dispharynx nasuta, Ornithostrongylus quadriradiatus, Strongyloides avium, Syngamus trachea, and Tetrameres fissispina), cestodes (Dicranotaenia coronula, Diorchis stefanskii, Fimbriaria fasciolaris, and Raillietina cesticillus, Sobolevicanthus gracilis), trematode (Echinostoma revolutum), and protozoa (Cryptosporidium baileyi). Although no study effectively proved cross-transmission either experimentally or by genetic analysis, these parasites demonstrate low host specificity and a high potential for parasite sharing. There is potential for parasite sharing whenever determinants such as host specificity, life cycle, and husbandry are favorable. More research should be carried out to describe parasites in both captive and free-ranging birds in zoological settings and the likelihood of cross-infection. Such information would contribute to evidence-based control measures, enhancing effective husbandry and preventive medicine protocols. J. Adv. Vet. Anim. Res., 7(3): 482-500, Sep 2020 http://doi.org/10.5455/javar.2020.g445